On the perpetual strangeness of the Bible - Edwards, Michael (University of Virginia Press, 2023)
"On the Perpetual Strangeness of the Bible offers a close reading of some of the more perplexing passages in the Bible, from the Wisdom writings to the enigmatic book of Revelation. Edwards explores the apparently simple instruction in Proverbs to eat honey and reveals unexpected complexity. He sounds the unfathomable depths of St. Paul's revelation that the Christian has "died" and yet now lives in Christ-and goes on to ask what it would mean to take the awesome expression "the kingdom of heaven is at hand" seriously. Three final meditations complete these meditations by scrutinizing the visionary world of Revelation"--